CONFLICT ANALYSIS OF THE MAIN CHARACTER IN THE PICTURE OF DORIAN GRAY BY OSCAR WILDE: KENNEY CONFLICT THEORY - Alfina Hidayati; Titis Setyabudi (Universitas PGRI Palembang, 2025)
The primary objectives of this study are to identify and analyze the conflicts encountered by the protagonist in The Picture of Dorian Gray by Oscar Wilde through the lens of Kenney’s Conflict Theory, to examine how the main character constructs and contributes to these conflicts throughout the narrative, and to explore how these conflicts influence the protagonist’s character development. The research employs several data collection methods, including close reading, systematic coding and categorization, thematic analysis, and interpretative strategies. The findings reveal a total of nine external and four internal conflicts depicted in the novel. The narrative structure follows a conventional progression encompassing exposition, the central conflict, rising action, climax, falling action, and resolution. The character development of the protagonist is portrayed through significant psychological transformation as the plot unfolds. This transformation is marked by a dynamic emotional journey, encompassing a range of sentiments such as joy, remorse, fear, admiration, jealousy, awe, love, and enthusiasm.